Preoperative anesthetic clinical evaluation and its importance – patient’s perspective - Pereira, Luís Guimarães; Pinho, Cristiana; Moreira, Adriano; Passos, Madalena (Journal of the Portuguese Society of Anesthesiology, 2015)
Introduction: The main purpose of preoperative anesthetic clinical evaluation is to evaluate patients scheduled for surgery requiring anesthesia. Although its current establishment in the majority of hospitals, patient’s opinion about preoperative clinical evaluation has been studied to a small extent. The goals of our study were: to assess the patient’s opinion about the preoperative clinical evaluation and to identify fears and concerns related with anesthesia. Material and Methods: Application of a questionnaire at the end of the preoperative evaluation, after ethical approval. Patients were questioned about fears and concerns related with anesthesia, satisfaction and importance attributed to preoperative anesthetic clinical evaluation, and satisfaction about the procedure explanation provided by the surgeon, in a 5-point Likertscale. Age, gender, educational level, surgical specialty, American Society of Anesthesiologists (ASA) physical status and previous anesthesia were registered. We used descriptive statistics to summarize data, and Χ2 test for hypothesis testing. Results: We have obtained 782 questionnaires. Concerning satisfaction with preoperative anesthetic clinical evaluation, 58.4% were “satisfied” and 40.6% “completely satisfied”. About importance attributed, 59.3% answered “important” and 37.1% “very important”. Relatively to fears and concerns, 17.5% answered “unable to wake”, 9.7% “to have pain”, and 57.4% of patients denied any fear or concern.Discussion and Conclusion: Globally, the satisfaction and importance attributed to preoperative anesthetic evaluation were high. The majority of our patients did not present fears or concerns about anesthesia.